Concise Review: Quantitative Detection and Modeling the In Vivo Kinetics of Therapeutic Mesenchymal Stem/Stromal Cells. (6th December 2017) - Brooks, Anastasia; Futrega, Kathryn; Liang, Xiaowen; Hu, Xiaoling; Liu, Xin; Crawford, Darrell H. G.; Doran, Michael R.; Roberts, Michael S.; Wang, Haolu
Abstract : Mesenchymal stem/stromal cells (MSCs) present a promising tool in cell-based therapy for treatment of various diseases. Currently, optimization of treatment protocols in clinical studies is complicated by the variations in cell dosing, diverse methods used to deliver MSCs, and the variety of methods used for tracking MSCs in vivo. Most studies use a dose escalation approach, and attempt to correlate efficacy with total cell dose. Optimization could be accelerated through specific understanding of MSC distribution in vivo, long-term viability, as well as their biological fate. While it is not possible to quantitatively detect MSCs in most targeted organs over long time periods after systemic administration in clinical trials, it is increasingly possible to apply pharmacokinetic modeling to predict their distribution and persistence. This Review outlines current understanding of the in vivo kinetics of exogenously administered MSCs, provides a critical analysis of the methods used for quantitative MSC detection in these studies, and discusses the application of pharmacokinetic modeling to these data. Finally, we provide insights on and perspectives for future development of effective therapeutic strategies using pharmacokinetic modeling to maximize MSC therapy and minimize potential side effects.